Evaluasi Kebijakan Penanggulangan Bencana: Studi Program â€œDesa Tangguh Bencanaâ€ di Desa Panimbangjaya, Kabupaten Pandeglang - Siti Humaeroh (Journal of Citizenship, 2025)
Desa Tangguh Bencana (Destana) is a community-based national policy aimed at strengthening preparedness in facing disaster risks. This study aims to evaluate the implementation of Destana in Panimbangjaya Village, located in Pandeglang Regency. Panimbangjaya is one of the villages on the southern coast of Pandeglang Regency that is highly vulnerable to hydrometeorological disasters. The proximity of the Indo-Australian and Eurasian tectonic plates makes this region frequently affected by earthquakes. This condition makes the Disaster-Resilient Village Program (Destana) critically important as the first line of mitigation for thousands of residents in the area. This research employs a descriptive qualitative method. Data were collected through in-depth interviews and documentation. The findings indicate that the training and outreach activities under the Destana program have improved the community's understanding of disaster mitigation. However, limited funding, inadequate evacuation infrastructure, and low community participation remain major challenges. A lack of village fund allocation and dependence on external facilitators also constrain the programâ€™s sustainability. The study recommends implementing integrated educational programs involving formal educational institutions and community organizations, improving infrastructure to facilitate evacuation mobility, and promoting local economic empowerment as a comprehensive approach to building sustainable village resilience. Overall, the program has shown results, particularly in increasing public knowledge on disaster preparedness, but technical issues such as budgeting remain serious challenges.